2017
DOI: 10.1590/1980-5497201700030005
|View full text |Cite
|
Sign up to set email alerts
|

Pesquisa Nacional de Saúde 2013: relação entre uso de álcool e características sociodemográficas segundo o sexo no Brasil

Abstract: ABSTRACT:Objective: To analyze sociodemographic factors associated with alcohol use according to gender in Brazil. Methods: Cross-sectional study using data from 2013 Brazilian Health Survey about 60,202 adults. We analyzed recent alcohol use and heavy episodic drinking in the 30 days prior to the research stratified by gender. The covariates were: age, educational level, skin color, marital status, and place of residence. Results:The prevalence of recent alcohol use was 26.5%. In women, the prevalence was 14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 26 publications
0
15
0
19
Order By: Relevance
“…Among the associated factors, the present study found that men were more likely to consume alcohol in an excessive and episodic way than women. Despite the difficulties in comparisons, due to the fact that few studies have analyzed the age range of this investigation, other studies have shown similar results, revealing a higher prevalence of alcohol abuse among men compared to women 12 . According to Garcia and Freitas 11 , this difference between the sexes is explained by the fact that men abstain less from alcoholic beverages and drink alcohol with great frequency and quantity.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Among the associated factors, the present study found that men were more likely to consume alcohol in an excessive and episodic way than women. Despite the difficulties in comparisons, due to the fact that few studies have analyzed the age range of this investigation, other studies have shown similar results, revealing a higher prevalence of alcohol abuse among men compared to women 12 . According to Garcia and Freitas 11 , this difference between the sexes is explained by the fact that men abstain less from alcoholic beverages and drink alcohol with great frequency and quantity.…”
Section: Discussionmentioning
confidence: 51%
“…With regard to the risk factors associated with BD, it is possible to point to age, gender 12 , religion 13 , schooling 14 and smoking 15 , and which, when combined, reveal the profile of the group that is most susceptible to practicing this type of consumption. RESUMO: Objetivo: Avaliar a prevalência e fatores associados ao consumo excessivo episódico de álcool (CEEA) entre jovens brasileiros.…”
Section: Introductionmentioning
confidence: 99%
“…Brazil exceeds the average of the Americas in relation to the annual consumption of pure alcohol per inhabitant over the age of 15, and the use of alcohol in the country is the fourth risk factor for the global disease load. There are more alcohol consumers in the higher socioeconomic groups of these countries, while abstention is greater in the less favored social groups (16)(17) .…”
Section: Population Data Availabilitymentioning
confidence: 99%
“…Analysis of the GSHS data pool conducted by the WHO found predominance of recent higher alcohol use in males, in relation to females, in all WHO regions 17 . However, studies with the Brazilian adult population show that, over the years, boys tend to outperform girls in relation to this behavior 18,19 . Thus, the relationship between alcohol consumption and the gender variable should continue to be monitored, as it may be a cohort effect due to new gender identity tendencies 20 .…”
Section: Discussionmentioning
confidence: 99%